Disney's : The Little Mermaid - Published by Grolier Book Club Edition (Denmark Grolier Book Club Edition, 1993)
A little sea princess, longing to be human, trades her mermaid's tail for legs, hoping to win the heart of the prince she loves
Include Color Illustrations